Kontruksi Pemikiran Pendidikan Imam Zarkasyi Sebagai Reformasi Pesantren - Mustafidah, Nur Mashani; Susanto, M. Arif (STIT Muhammadiyah Paciran Lamongan, 2022)
The study describes Imam Zarkasyi's thought of reconstruction of pesantren reform. This study aims to explore Zarkasyi's thoughts to be implemented as a model of Islamic education reform for the modernization of Islamic society. The limitations of this research are the Zarkasyi curriculum, empowerment of organizational management, and ethics training in Islamic boarding schools. The findings were revealed in three main points. First, Zarkasyi believes that the Islamic Education curriculum should cover religious principles, as well as modern science. Thus, students are expected to master Arabic and English. Second, the management of the organization and waqf requires significant improvements to strengthen pesantren institutions in accordance with modern principles. Third, pesantren education emphasizes the values of sincerity, simplicity, independence, togetherness, and freedom to foster ethical awareness in Islamic education schools. The values above are expected to become the hallmarks of the Gontor Islamic Boarding School graduates.